RITUAL SEBAGAI MEDIA KONSTRUKSI IDENTITAS: Suatu Perspektif Teoretisi - Yance Z. Rumahuru (DIALEKTIKA, 2020)
ABSTRACT This paper is a critical effort made to respond to the reality of what happened in Maluku related to the widespread development of capitalism. With reviews that uses narrative approach, then this article seeks to present issues related to the influence of capitalism and the hegemonic power (governmental) on the Maluku people who have an impact on the welfare and comfort of their lives, a small community. It must be recognized that this writing is still far from eligibility as a good writing. However, with the existing shortcomings we try to explain it, assisted by the use of the theory of the takeover secretly (the silent take over), Hertz and hegemony (Gramsci), so this article can explain about problems multiulturalisme as teriadi in Maluku. Keywords: Capitalism, Hegemony of Power, Multiculturalism, Small Community Rights